2022
DOI: 10.3389/feduc.2022.973274
|View full text |Cite
|
Sign up to set email alerts
|

E-leadership of the school principals in implementing online learning during COVID-19 pandemic at public senior high schools

Abstract: This research aimed to discover the implementation of e-leadership for school principals during the COVID-19 pandemic and its effect on school performance through changes in teacher behavior. Quantitative research was used where it involved 8 public high schools with 150 respondents. The results showed that: (1) the implementation of e-leadership for school principals during the COVID-19 pandemic was at a very high level for the dimensions of the vision of continuous learning and professional development of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…In addition to integrating AI technologies into their management and leadership practices, principals are equally expected to promote their use by teachers through changing their attitudes and behaviors (Indra et al, 2022;Karakose et al, 2024;Polat et al, 2022). As underlined by Jameson et al (2006) it is not only the absence of necessary technological infrastructure or digital tools but also the failure of teachers to internalize their contribution to teaching/learning.…”
Section: Implications Of Ai For School Leadership and Managementmentioning
confidence: 99%
“…In addition to integrating AI technologies into their management and leadership practices, principals are equally expected to promote their use by teachers through changing their attitudes and behaviors (Indra et al, 2022;Karakose et al, 2024;Polat et al, 2022). As underlined by Jameson et al (2006) it is not only the absence of necessary technological infrastructure or digital tools but also the failure of teachers to internalize their contribution to teaching/learning.…”
Section: Implications Of Ai For School Leadership and Managementmentioning
confidence: 99%
“…Data yang dijelaskan di atas selaras dengan kesimpulan yang ditemukan dari beberapa penelitian yang menjelaskan bahwa monitoring terhadap guru dapat dilakukan melalui perangkat pembelajaran yang mereka buat (Arman et al, 2021). Kepala sekolah dalam posisinya sebagai supervisor mesti melakukan evaluasi dan monitoring terhadap kinerja guru yang berada di bawah binaannya (Egwu, 2015), dalam hal ini Indra dan kawan-kawan menegaskan bahwa kepala sekolah mesti memberdayakan segala sumber daya yang ada di lingkungan sekolah yang dipimpinnya (Indra et al, 2022).…”
Section: Desain Pembelajaran Pendidikan Agama Islam Sd Sekecamatan Ba...unclassified
“…Rusman et al revealed that in order to build international standard educational institutions, in addition to a strong commitment, leaders must also be supported by human resource management [27]. Other studies focus on leadership in educational institutions in the technological era requiring technological skills [28,29].…”
Section: Introductionmentioning
confidence: 99%